Modified Smith predictor‐based P‐PD control for pure integrating delay dominated processes. (1st November 2021) - Karan, Somak; Dey, Chanchal
Abstract: Modified Smith predictor (MSP) with P (proportional)‐PD (proportional‐derivative) control methodology is designed for pure integrating processes with time delay (IPTD). Industrial processes such as liquid supply to the large storage, fractional distillation, and superheated steam flow to turbine are found to be integrating in nature with dominant time delay. The proposed P‐PD control strategy ascertains the desired closed loop response. The closed loop time constant ( λ ) is considered to be the sole tuning parameter for reducing the tuning intricacies of the proposed MSP‐based design. P controller in the forward path is tuned by the internal model control (IMC) technique towards enhanced servo tracking. In the feedback path, PD controller parameters are obtained from Routh's stability analysis for improving regulatory responses. Overshoot free set point response is observed and smooth as well as reasonably faster recovery is also found during load fluctuations. Effectiveness of the proposed MSP is validated during closed loop performance and stability analyses in comparison to others' reported dead time compensating methodologies.